Participation of young voters in nest state general election in Sarawak / Christina Muti Alexander & Joel Pengiran Ejau - Alexander, Christina Muti; Ejau, Joel Pengiran (2014)
Voting or election plays a big role in every country, to determine who will be chosen to lead the country and to take of the welfare of the country and its people. Election can be defined as the ability of the people to cast their votes to elect and select an individual for a position. It is the act of choosing or selecting one or more from a greater number of persons, things, courses, or rights. The choice of an alternative, (Slate v. Tucker, 54 Ala.210) Young voters or youth vote is the term used in politics to characterize a group of young voter which are aged between 18-29 years old who are involve in the political engagement. However in Malaysia the age of voters starts at the age of 21.